Pengaruh Metode Pembelajaran dan Kecerdasan Linguistik Terhadap Kemampuan Bahasa Arab Siswa Kelas II SDIT Anak Sholeh - Royidi, Ayif (JTP - Jurnal Teknologi Pendidikan, 2016)
The purpose of this research is to find out the influence of Three-ber method and linguistic intelligence implementation on Arabic students learning Ability of Arabic language. The research is comparative quantitative with the experimental methods and 2 x 2 by level design .A test is the instrument, used to gather the linguistics data intelligence and student Ability of Arabic language. ANAVA is applied for hypothesis testing two lanes continued to Tukey Test .The results of the study (1) .The Students who learn Arabic trough Three-ber method achieve better than the students who is being taught conventionally(2) There is an interaction between learning method and linguistics intelligence(3)The students whose high linguistic intelligence and learn using Three-ber method achieve better than the students who learn conventionally(4). Arabic students learning Ability of Arabic language whose low linguistic intelligence and learn using Three-ber method achieve lower than student who is being taught conventionally.